2015
DOI: 10.1186/s13019-015-0293-y
|View full text |Cite
|
Sign up to set email alerts
|

One-year patency control and risk analysis of eSVS®-mesh-supported coronary saphenous vein grafts

Abstract: BackgroundThe eSVS® external venous nitinol mesh (Kips Bay Medical, Minneapolis, USA) was designed to improve long-term patency of coronary saphenous vein grafts (SVG) by preventing pressure-induced wall stress and reactive neo-intimal hyperplasia. We present one-year-patency rates of meshed SVGs assessed by coronary computed tomographic angiography (cCTA).Patients and MethodsData from consecutive patients receiving an eSVS® meshed coronary bypass SVG from 06/2010 to 06/2011 were prospectively collected and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Meanwhile, all three stented grafts occluded after 8 weeks implantation may resulted from intimal hyperplasia or other factors. These results indicated that the external stents could maintain the straight vascular structure and While in recent decades, the product of eSVS (Kipsbay Medical Inc., MN, USA) has been studied in a number of randomized trials, which indicated that patency ratio of stented grafts was high in early times but decreased in the long-term observation (15,17,18,22). Studies on VEST (Vascular Graft Solutions LD, Tel Aviv, Israel), the newly designed stent, have shown that the intimal hyperplasia was dramatically reduced in stented grafts, while it had an equal effect on graft patency compared to non-stented grafts (19,20,37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, all three stented grafts occluded after 8 weeks implantation may resulted from intimal hyperplasia or other factors. These results indicated that the external stents could maintain the straight vascular structure and While in recent decades, the product of eSVS (Kipsbay Medical Inc., MN, USA) has been studied in a number of randomized trials, which indicated that patency ratio of stented grafts was high in early times but decreased in the long-term observation (15,17,18,22). Studies on VEST (Vascular Graft Solutions LD, Tel Aviv, Israel), the newly designed stent, have shown that the intimal hyperplasia was dramatically reduced in stented grafts, while it had an equal effect on graft patency compared to non-stented grafts (19,20,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…After seeing several promising results in animal studies (11)(12)(13)(14), more and more researchers are concentrating on the therapy of using external stents on patients who receive CABG. However, the studies on humans presented contradictory results (15)(16)(17)(18)(19)(20). Besides stent-fabricating materials, which are usually polymers or alloys, another important factor influencing stent efficacy is the diameter of an external stent.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous clinical results were mixed, and even reported increased SVG failure rates. [23][24][25] On the contrary, Taggart and colleagues, 26 using a new cobalt-chromium venous external stent, recently presented favorable data on the concept of external stenting that showed a significant reduction in intimal hyperplasia at 1 year by intravascular ultrasonography. However, large-scale and longer-term studies are needed to validate these findings and it is important to recognize that such techniques add further complexity to the CABG procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The CTA patency rate was 92% [ 74 ]. Inderbitzin et al reported the 1-year follow-up in 19 of 22 surviving patients who had received the mesh with overall 1-year CTA patency rate of 21 eSVS ® meshed SVGs being 76% [ 75 ]. Larger randomised studies with longer term follow-up are needed however before more widespread clinical adoption of such devices.…”
Section: Factors Predisposing To Svg Failurementioning
confidence: 99%